2017
DOI: 10.1371/journal.pone.0174020
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive measurements of disease progression in rare disorders: Developing and validating a multimodal model of retinal degeneration in Stargardt disease

Abstract: BackgroundEach inherited retinal disorder is rare, but together, they affect millions of people worldwide. No treatment is currently available for these blinding diseases, but promising new options—including gene therapy—are emerging. Arguably, the most prevalent retinal dystrophy is Stargardt disease. In each case, the specific combination of ABCA4 variants (> 900 identified to date) and modifying factors is virtually unique. It accounts for the vast phenotypic heterogeneity including variable rates of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Any preventative treatment of this group would need to balance the risk of treating some of these patients who might not lose significant acuity for several years untreated, with the potential benefits to those who eventually do lose their foveal sparing. With the p.N1868I allele accounting for a significant number of patients with Stargardt disease, the relative homogeneity of this group of patients should lend itself to longitudinal studies of visual acuity loss as well as more sensitive biomarkers, such as progression of macular atrophy, 10,30,40 conceivably leading to treatment trials requiring smaller numbers of patients than might otherwise be required to demonstrate efficacy. Delineating the prognosis of these patients may also suggest that one particular avenue of treatment, such as gene therapy, stem-cell transplantation, or pharmacological approaches, 41 may be more appropriate than others for this foveal-sparing form of Stargardt disease.…”
Section: Resultsmentioning
confidence: 99%
“…Any preventative treatment of this group would need to balance the risk of treating some of these patients who might not lose significant acuity for several years untreated, with the potential benefits to those who eventually do lose their foveal sparing. With the p.N1868I allele accounting for a significant number of patients with Stargardt disease, the relative homogeneity of this group of patients should lend itself to longitudinal studies of visual acuity loss as well as more sensitive biomarkers, such as progression of macular atrophy, 10,30,40 conceivably leading to treatment trials requiring smaller numbers of patients than might otherwise be required to demonstrate efficacy. Delineating the prognosis of these patients may also suggest that one particular avenue of treatment, such as gene therapy, stem-cell transplantation, or pharmacological approaches, 41 may be more appropriate than others for this foveal-sparing form of Stargardt disease.…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 18 , 19 Furthermore, the identification of RPE atrophy in ABCA4 -related retinopathy appears to be more challenging as it encompasses variable stages toward complete atrophy ranging from questionable (QDAF) to definitely (DDAF) decreased AF. 20 , 21 A previous study correlated OCT-findings in QDAF and DDAF and found significantly thinner outer retinal layers (outer nuclear layer and combined layers between external limiting membrane and Bruch's membrane) in the latter case, considering QDAF as a transition state between healthy retina and DDAF. 22 As both RPE atrophy manifestations may be present within the same eye, more sophisticated measurement approaches are required.…”
Section: Introductionmentioning
confidence: 83%
“…22 As both RPE atrophy manifestations may be present within the same eye, more sophisticated measurement approaches are required. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…Microperimetry with static perimetry may provide detailed functional testing in the macula but is also time-consuming, and Stargardt patients have less well-defined correlation between structure and function than patients with age-related macular degeneration 57 59 . Thus, combining structural and functional outcomes may be more sensitive to changes than a single mode of testing alone 60 . As above, our data demonstrate an overall slow rate of retinal change (e.g., 3 microns/year for outer retina thinning) in patients with STGD1.…”
Section: Discussionmentioning
confidence: 99%